Transformasi Epistimologi Hukum Islam Klasik: Rekostruksi Metodologis Untuk Yurisprudensi Kontemporer - Arinalhaq, Muhammad Syauqi; Suadi Saad; Endang Saeful Anwar (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
This study aims to examine the evolution of Islamic law in the classical period, analyze its sources and methods, and review the extent of its influence on contemporary jurisprudence. This research employs a qualitative method with historical, normative, and epistemological approaches. The findings indicate that the development of Islamic law in the classical era emerged from the interaction between sacred texts, rational reasoning, and socio-historical conditions. Various schools of thought that arose at that time demonstrated distinctive characteristics while maintaining adherence to the fundamental principles of law. The study further reveals that the concept of maqāṣid al-sharī‘ah had been employed by classical scholars to formulate laws that remained relevant to the needs of their society. The novelty of this research lies in the epistemological reconstruction of classical Islamic law, which is proposed as a new methodological framework for contemporary jurisprudence. It emphasizes that modern ijtihad does not merely replicate classical legal products but rather integrates maqāṣid principles and interdisciplinary approaches to address the complexities of social, economic, political, and cultural transformations. The theoretical implication of these findings is the need to reposition the epistemology of Islamic law from a purely textual-normative paradigm toward a contextual-adaptive paradigm that is more responsive to contemporary challenges. Thus, this study contributes to the development of modern Islamic law by offering a methodological framework that is critical, dynamic, and relevant to the demands of a global society.